PHYLOGENETIC RELATIONSHIPS AMONG (GRAPEVINE) Vitis TAXA BASED ON RANDOM AMPLIFICATION OF POLYMORPHIC DNA (RAPD-PCR) MARKERS - Al- Anbari, Aseel K.; Al_ Zubaidy, Mohanad W.; Al-Zubaidy, Najm A.; Sultan, Ammar A.; Mohammed, Shereen M. (Diyala Agricultural Sciences Journal, 2017)
Phylogentic relationships among seven genotypes of Vitis were analyzed by RAPD-PCR markers, DNA of fresh young leaves was extracted from each sample for RAPD analysis. Performed with 20 decamer primers selected six primers that showed clear results. A total sixty eight bands were produced out of which forty eight bands were polymorphic, The dendrogram reveals that grapevine taxa separated to main groups (A and B), the first group includes the most of taxa were Vitis hissarica Vass., V. hissarica subsp. rechingeri, V. sylvestris Fl. Bed., V. vinifera L. (Native), and V. vinifera var. sativa Beck., while group B contains 2 species were V. coignetiae Planch., and V. berlandieri Pulliatt. The taxa V. hissarica and V. hissarica subsp. rechingeri have been recorded closest genetic distance matrix among taxa under study with similarity range 0.11. The results of this study were offered an important data in taxonomy and may be can be a phylogenetic key to isolating the taxa. Moreover it is provide basic information for future genetic studies such as gene expression profiling.